SASTRA LISAN MANTRA PENGOBATAN DI KENAGARIAN TALU KECAMATAN TALAMAU KABUPATEN PASAMAN BARAT - Afdal Agus; Bakhtaruddin Nasution; Muhammad Ismail Nasution (Faculty of Languages and Arts, Universitas Negeri Padang, 2013)
This research aims to describe the (1) the structure of the text spells treatment, (2) supporting aspects spells reading of treatment, (3) the treatment of inheritance spells. This research uses a qualitative approach with descriptive methods. Data were collected through observation, interviews, and recording. The results showed that the structure of the text spells treatment consists of: the opening section, part of the contents, and the end. Supporting aspects spells reading of treatment in Kenagarian Talu found: (1) time: free, wherever, (2) actors: shaman himself, (3) events: be seated, standing and kneeling, (4) where: in shaman home and patient home, (5) clothing: white clothes and free, (6) fixtures: medicine fit the type of illness, medicine is attached and drunk, (7) how to bring spell: slowly, cautiously, and whispered. Inheritance process of treatment spell is divided into two, (1) spells obtained from the parents, but some are obtained from family members, such as brothers, and (2) generally passed on to children.